Demography of Dhampus: A Community Health Diagnosis Field Visit Report - Poudel, S; Ghimire, U R; Sanjeeb, K C; Kunwar, S; Mehta, R; Niraula, S; Yadav, R; Parajuli, R; Regmi, S; Bohara, S; Subedi, S; Chimariya, S; et al. (Journal of Gandaki Medical College-Nepal, 2018)
Community health diagnosis is a comprehensive assessment of health status of the community in relation to its social, physical and biological environment. The purpose of community health diagnosis is to define existing problems, determine available resources and set priorities for planning, implementing and evaluation health action, by and for the community. A cross sectional descriptive study was done at Dhampus VDC from 1 Sept 2016 AD (16th Bhadra, 2073 BS) to 16 Sept 2016 AD (31st Bhadra, 2073). The data was collected by questionnaires, anthropometric measurements, interviews and secondary data. The community health diagnosis field visit gave us the opportunity to build our team spirit and taught us the arts of problem solving. It taught us the importance of correct conduct and building a good rapport with the people who were unfamiliar to us. J-GMC-N | Volume 11 | Issue 01 | January-June 2018, Page: 71-76